2013
DOI: 10.1097/hpc.0b013e3182a78c06
|View full text |Cite
|
Sign up to set email alerts
|

Resource Consumption and Healthcare Costs of Acute Coronary Syndrome

Abstract: The objective of this study was to estimate resource consumption and direct healthcare costs of patients with a first hospitalization for acute coronary syndrome (ACS) in 2008 in the Piedmont Region, Italy. Subjects hospitalized with a first episode of ACS in 2008 were selected from the regional hospital discharge database. All hospitalizations, drug prescriptions, and outpatient episodes of care in the 12 months following discharge were considered to estimate resource consumption and direct healthcare costs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…This is perhaps further evidenced by the positive association between hospitalization in the 3 months prior to the index event and high costs. Similar findings for male sex are consistent with a study in Italy where costs incurred by men were significantly greater than that for women, irrespective of index-event type [ 8 ]. Reports that women who present with ACS may be evaluated less intensively than men, may go some way towards explaining this [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is perhaps further evidenced by the positive association between hospitalization in the 3 months prior to the index event and high costs. Similar findings for male sex are consistent with a study in Italy where costs incurred by men were significantly greater than that for women, irrespective of index-event type [ 8 ]. Reports that women who present with ACS may be evaluated less intensively than men, may go some way towards explaining this [ 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Evidence from the US, comparing inpatient resource use for ACS in patients who died in hospital with that for a surviving ACS cohort, indicated that inpatient mortality for ACS is associated with a 47% greater duration of hospital stay along with an incremental cost of around US$43,000 [ 7 ]. Similarly, in a study conducted in Italy, which followed up patients for 12 months’ post-hospitalization for ACS, patients who died of a cardiovascular event had an average cost of around €16,000 compared with an average cost of around €11,000 for the entire ACS cohort [ 8 ]. In China, a small study in a single hospital in Shandong found that increased age was associated with increased treatment costs and poorer clinical outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“… 37 An Italian real-world study, performed in 2008, showed that direct health care costs were at least 50% higher in patients with a recurrent ACS compared with patients without recurrent ACS. 38 In particular, Roggeri et al 38 showed that, in an Italian health care setting, the average yearly costs per patient alive at the end of the follow-up period and in treatment with DAPT were €20,554 in the group of patients with recurrent ACS and €13,303 in the group of patients without recurrent ACS, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There are several recent studies that have examined the costs of CVD-related events, and especially so with a focus on short-term healthcare costs due to CVD-related events [ 3 10 ]. These studies have not included patients based on a diagnosis of or treatment for hyperlipidemia but instead included patients hospitalized for CV events [ 3 , 10 , 11 ], patients with atherosclerosis [ 4 ], hypertension [ 5 ], or acute coronary syndrome [ 6 , 7 , 12 ], or used a prevalence-based approach [ 8 , 9 ]. Only a few studies have examined the long-term costs associated with CVD-related events [ 3 , 10 , 11 ] and stratified by specific event types [ 13 ].…”
Section: Introductionmentioning
confidence: 99%